2014
DOI: 10.1371/journal.pone.0086333
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Peripheral Expression of the Glucocorticoid Receptor α Isoform in Individuals with Posttraumatic Stress Disorder: A Cumulative Effect of Trauma Burden

Abstract: BackgroundPosttraumatic stress disorder (PTSD) is a serious psychiatric condition that was found to be associated with altered functioning of the hypothalamic-pituitary-adrenal (HPA) axis and changes in glucocorticoid (GC) responsiveness. The physiological actions of GCs are primarily mediated through GC receptors (GR) of which isoforms with different biological activities exist. This study aimed to investigate whether trauma-experience and/or PTSD are associated with altered expression of GR splice variants.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…The mRNA levels of GR-b, as opposed to GR-a, were extremely low in both CAD patients and controls. This is in agreement with previous studies showing that GR-b mRNA levels in PBMCs are up to 2000 times lower than GR-a mRNA levels [33,34]. Upregulated levels of GR-b have been associated with glucocorticoid unresponsiveness in cell line models and glucocorticoid-resistant forms of diseases, such as asthma, rheumatoid arthritis and inflammatory bowel disease [12,[35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…The mRNA levels of GR-b, as opposed to GR-a, were extremely low in both CAD patients and controls. This is in agreement with previous studies showing that GR-b mRNA levels in PBMCs are up to 2000 times lower than GR-a mRNA levels [33,34]. Upregulated levels of GR-b have been associated with glucocorticoid unresponsiveness in cell line models and glucocorticoid-resistant forms of diseases, such as asthma, rheumatoid arthritis and inflammatory bowel disease [12,[35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…This notion is supported by a study reporting significantly decreased GRα mRNA expression in participants with PTSD compared to healthy controls. Of particular relevance to the current work is the finding that decreased GRα expression was modulated by a dose-response effect of trauma irrespective of PTSD status, such that those with higher trauma loads showed more marked decrease in GRα expression (Gola et al, 2014). …”
Section: Discussionmentioning
confidence: 85%
“…While expression of the inactive GRβ plays an important role in inflammatory disorders, expression of GRα has been associated with stress-related and psychiatric disorders. There are no other published studies of GR mRNA in IBS, but lower PBMC GRα mRNA was also found in association with fibromyalgia (Macedo et al, 2008), which has shared pathophysiology with IBS, and in post-traumatic stress disorder (Gola et al, 2014). Limited evidence for a link between peripheral and central GR expression exists (Hepgul et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(Johnson and Greenwood-Van Meerveld, 2015) In humans, decreased central expression of GRs has been associated with depression in findings from autopsy specimens, (Webster et al, 2002) and impaired negative feedback in depression is also supported by the consistent response to dexamethasone suppression or dexamethasone-CRF testing. Though negative feedback is mediated by GRs in the central nervous system, changes in peripheral blood mononuclear cell (PBMC) GR number, (de Kloet et al, 2007) sensitivity, (Yehuda et al, 2004) promoter methylation status, (Yehuda et al, 2015) and mRNA expression (Gola et al, 2014; Hepgul et al, 2013) have been reported in psychiatric disease associated with negative feedback of the HPA axis. While studies in IBS have not supported impaired negative feedback based on dexamethasone suppression, (Bohmelt et al, 2005; Dinan et al, 2006) PBMC GR mRNA expression has not been studied.…”
Section: Introductionmentioning
confidence: 99%